METHOD OF MAUT IN DETERMINING THE RANK OF CHILDREN AND HEALTHY ELDERLY AT PETATAL PUSKESMAS - Latifah Hanum; Mohd Siddik; Cecep Maulana (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: The current development of information technology has had an impact on all fields, including the health sector. Many activities that were previously carried out conventionally or manually can now be carried out with the help of technology. Computers that were previously only used to process data now provide many services, applications, and programs that can help facilitate human activities. One of them is the Multi-Attribute Utility Theory (MAUT) method, which is a support system method that has been widely used to provide accurate and efficient results. This study aims to build a decision support system for choosing healthy toddlers and elderly at the Petatal Health Center, Talawi District, Asahan Regency. So far, the process of selecting healthy toddlers and elderly is done conventionally, without the help of applications or computer programs. So the time needed is longer and the results are also less objective. The calculation process uses the MAUT method with an alternative of 13 toddlers and 15 elderly. The criteria used are body weight, nutritional status, potassium content, protein content, and carbohydrate content. Assessment weight 1-5. The results are 3 Toddlers with the highest total score Laila (17) Putri Sundar (14.25) and Tiara with a score of 12.25. The three people with the highest scores for healthy elderly are Rini Dewi with a score of 17, Joni with a score of 14.25, and Bejo Asmo with a value of 12.25.            Keywords: decision support system; MAUT; multi atribute utility theory; SPK Abstrak: Perkembangan Teknologi informasi saat ini telah berdampak pada semua bidang, termasuk bidang kesehatan. Banyak kegiatan yang awalnya dilakukan secara konvensional atau manual kini dapat dilakukan dengan bantuan teknologi. Komputer yang tadinya hanya digunakan untuk mengolah data kini menyediakan banyak layanan, aplikasi dan program yang dapat membantu mempermudah kegiatan manusia. Salah satunya adalah metode Multi Atribute Utility Theory (MAUT) yang merupakan salah satu metode sistem pendukung yang telah banyak digunakan untuk memberikan hasil yang akurat dan efisien. Penelitian ini bertujuan membangun sistem pendukung keputusan pemilihan Balita dan Lansia Sehat di Puskesmas Petatal Kecamatan Talawi Kabupaten Asahan, selama ini proses pemilihan balita dan lansia sehat dilakukan secara  konvensional, tanpa menggunakan bantuan aplikasi atau program computer. Sehingga waktu yang dibutuhkan lebih lama serta hasilnya juga kurang objektif. Proses perhitungan menggunakan Metode MAUT dengan alternative 13 Balita dan 15 lansia .Kriteria yang digunakan Berat Badan, Status Gizi, Kandungan Kalium, Kandungan protein dan kandungan karbohidrat. Bobot penilaian 1-5. Hasil adalah 3 Balita dengan total nilai tertinggi Laila (17) Putri Sundar (14,25) dan Tiara dengan nilai 12,25. Tiga orang dengan nilai tertinggi untuk Lansia sehat adalah Rini dewi dengan nilai 17, Joni dengan nilai 14,25 dan Bejo Asmo dengan nilai 12,25. Kata kunci: multi atribute utility theory; MAUT; sistem pendukung keputusan; SPK